2020
DOI: 10.1126/sciadv.abc7646
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot spectral imaging with parallel metasystems

Abstract: Spectral imagers divide scenes into quantitative and narrowband spectral channels. They have become important metrological tools in many areas of science, especially remote sensing. Here, we propose and experimentally demonstrate a snapshot spectral imager using a parallel optical processing paradigm based on arrays of metasystems. Our multi-aperture spectral imager weighs less than 20 mg and simultaneously acquires 20 image channels across the 795- to 980-nm spectral region. Each channel is formed by a metasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 39 publications
(48 reference statements)
0
50
0
Order By: Relevance
“…Recent breakthroughs in the physics 7 11 and advancements in large-scale meta-optics fabrication 12 14 inspire a vision for a future in which meta-optics will be widely used. Recent studies have demonstrated cutting-edge technologies based on meta-optics platforms, such as polarization/light-field/depth imaging cameras 15 18 , metasurface-driven OLEDs 19 , virtual/augmented reality systems 20 , 21 , compact spectrometers 22 24 , etc. So far, the mainstream design of the meta-optics is mostly based on a “forward” methodology, in which one engineers each individual meta-atom component (as a phase shifter) independently, according to a predefined phase profile 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent breakthroughs in the physics 7 11 and advancements in large-scale meta-optics fabrication 12 14 inspire a vision for a future in which meta-optics will be widely used. Recent studies have demonstrated cutting-edge technologies based on meta-optics platforms, such as polarization/light-field/depth imaging cameras 15 18 , metasurface-driven OLEDs 19 , virtual/augmented reality systems 20 , 21 , compact spectrometers 22 24 , etc. So far, the mainstream design of the meta-optics is mostly based on a “forward” methodology, in which one engineers each individual meta-atom component (as a phase shifter) independently, according to a predefined phase profile 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Metasurface-based multi-layer systems, named metasystem, expand the functionality of metasurface in the out-of-plane dimension 38 40 . Lithographically assisted alignment and bonding between metasurface layers are required for providing sufficient precision and robustness in functional metasystems 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, compact spectrometers with nanometer spectral resolution based on a single metasurface have been demonstrated, which greatly reduces the weight and complexity of the system [27]- [29]. Subsequently, two kinds of spectral imagers utilizing metasurfaces have also been validated recently [30], [31]. One kind is a snapshot spectral imager, which is composed of three cascaded metasurface arrays [30].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, two kinds of spectral imagers utilizing metasurfaces have also been validated recently [30], [31]. One kind is a snapshot spectral imager, which is composed of three cascaded metasurface arrays [30]. The corresponding spectral resolution is 7 nm and thus this imager belongs to the hyperspectral system.…”
Section: Introductionmentioning
confidence: 99%